Psychodiagnostics in physical rehabilitation of students with spinal pathology - V.I. Kotelevskiy (Pedagogics, Psychology, Medical-Biological Problems of Physical Training and Sports, 2014)
Purpose : to determine the main directions and application methods psychodiagnosis with vertebral pathology students. Develop a program of psycho-diagnostics system in physical rehabilitation of students with spinal pathology. Material . The study involved 100 students 19-20 years old. Results . It is proved that the students (78%) exposed to stressful situations were more prominent functional changes of the spine. Found that patients with psychological testing ensures timely detection of a person's psychological. This allows for timely and efficient start rehabilitation activities and to choose the optimal method of psychological support in the process of physical rehabilitation. Conclusions . Complex application psychodiagnosis in three main areas (definition of personality traits, way to respond to stressful situations, determining the parameters of emotional background) allows differentiated and effectively in the process of psychological correction physical rehabilitation students.